Implementasi Augmented Reality Untuk Pengenalan Huruf Dan Angka Isyarat Untuk Anak SLB B - Andhi Yanto Wibowo; Murinto (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
exchange or delivery of information and messages from one party to another in order to understand each other between the two. Communication is usually done orally or verbally so that it can be understood by both parties. children with special needs, deaf in communicating have difficulty communicating and understanding messages, so they need to use language that suits their needs. Therefore the use of media to improve the ability of children with hearing impairments must be assisted by using media that can help children learn sign language by attracting students' attention and increasing interest in learning. This research uses the Multimedia Development Life Cycle method which has six stages. These stages are concept, design, material collecting, assembly, testing and distribution. This research utilizes Marker Augmented Reality technology as a tool to represent the introduction of the Sign Language System (SIBI). This application is used as a media or tool to help students learn to recognize letters and numbers in sign language. Based on the results of black box testing, all functions in this application have been running properly and are valid. Testing with the System Usability Scale (SUS) obtained a score of 85, so the application was declared ACCEPTABLE. Media expert testing gets a score of 91 with a percentage of 91% and can be categorized as very high so it is feasible to use. Material expert testing gets a score of 85% and is categorized as very high so it is feasible to use with revisions according to suggestions.